2018
DOI: 10.1111/ijfs.13790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactose content on dielectric properties of whole milk and skim milk

Abstract: Summary Dielectric properties (dielectric constant ε′ and dielectric loss factor ε′′) of whole milk and skim milk with the lactose content of 4.56–6.44% and 4.57–6.47%, respectively, were measured over the frequency range of 20–4500 MHz at 25 °C using a vector network analyzer. The results showed that ε′ decreased with increasing frequency, and ε′′ changed with V shape and its minimum was noted at about 2000 MHz. Whole milk had lower dielectric properties than skim milk at almost same lactose content and a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The reducing sugar content found on passion fruit pulp was 4.86%. This value is similar to the concentration of lactose content found on whole bovine milk, which is frequently used to ferment and growth of Lactobacillus reuteri culture [23]. Is important reinforce that reducing sugar present on passion fruit pulp is different from reducing sugar found in milk.…”
Section: Characterization Of Passion Fruit Pulp In Naturasupporting
confidence: 70%
“…The reducing sugar content found on passion fruit pulp was 4.86%. This value is similar to the concentration of lactose content found on whole bovine milk, which is frequently used to ferment and growth of Lactobacillus reuteri culture [23]. Is important reinforce that reducing sugar present on passion fruit pulp is different from reducing sugar found in milk.…”
Section: Characterization Of Passion Fruit Pulp In Naturasupporting
confidence: 70%
“…Dairy products exhibit different functional and physical properties, in which dielectric properties (DPs) is one of the main physical parameters. This property assists in predicting the heating rates of the material when exposed or subjected to high frequency in dielectric heating like a microwave ( Liu, Guo, & Zhu, 2018 ). The dielectric property (DP) as a function of temperature and frequency of dairy products including milk or whey-based powders was extensively studied by different researchers across the world ( Dag et al, 2019 , Liu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This property assists in predicting the heating rates of the material when exposed or subjected to high frequency in dielectric heating like a microwave ( Liu, Guo, & Zhu, 2018 ). The dielectric property (DP) as a function of temperature and frequency of dairy products including milk or whey-based powders was extensively studied by different researchers across the world ( Dag et al, 2019 , Liu et al, 2018 ). Besides this, another characterization technique is Fourier transform infrared spectroscopy (FTIR) which is widely performed for the estimation of functional groups in food samples ( Ostrowska-Ligęza, Górska, Wirkowska, & Koczoń, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the electric conductivity of milk has been used to detect the mastitis grades of dairy cows (Khatun et al, 2017), but the high false-positive rate makes it difficult for providing reliable results and cannot be used to quantitatively predict SCC. Several studies have shown that the dielectric properties of milk are closely related to its fat (Zhu et al, 2015b), protein (Zhu et al, 2015a), lactose (Liu et al, 2018), and salt (Zhu et al, 2018a) contents. Therefore, the dielectric spectra over a wide frequency range might provide more information related to SCC than the electric conductivity, and the dielectric spectra would be able to quantitatively detect the SCC of milk, but the potential has not been investigated.…”
Section: Introductionmentioning
confidence: 99%